Pengaruh Metode Ekstraksi Maserasi dan Infudasi terhadap Kadar Flavonoid Total serta Aktivitas Antioksidan Daun Kunyit (Curcuma Longa L.) - Angela Mericci Putri Budiarto; Danang Raharjo; Annie Rahmatillah (Jurnal Kesehatan Amanah, 2025)
Free radicals are known to contribute to a variety of degenerative diseases, including diabetes, cancer, and cardiovascular disease, as well as to the acceleration of the aging process. To counteract these effects, antioxidant compounds capable of neutralizing free radicals are essential. Turmeric leaf (Curcuma longa L.) is a promising source of natural antioxidants, as it is rich in flavonoid compounds that offer a range of important biological benefits. This study aimed to evaluate how different extraction methods influence the total flavonoid content and antioxidant activity of turmeric leaf extract, in order to identify the most effective technique. Two methods were used: maceration and infusion. The total flavonoid content was determined using the AlCl₃ colorimetric method, with quercetin serving as the standard. In vitro antioxidant activity was assessed using the ABTS method, and the results were measured by the total flavonoid content (expressed in mg quercetin equivalent (QE)/g of extract) and the IC₅₀ value, which indicates the strength of the antioxidant activity. The findings showed that the maceration method produced the highest flavonoid content, at 27.850 mg QE/g, and the best antioxidant activity, with an IC₅₀ value of 44.224 μg/mL. In contrast, the infusion method resulted in lower flavonoid content and antioxidant activity. This leads to the conclusion that the extraction method significantly impacts the quality of turmeric leaf extract, and maceration is the most effective technique for obtaining an extract with high flavonoid content and potent antioxidant activity.